Etika Ideal Murid dan Guru Perspektif KH. Muhammad Hasyim Asy’ari Tinjauan Kitab Adabul ‘Alim Walmuta’allim - Muhammad Ali Musafak (Jurnal Studi Islam dan Sosial, 2020)
The teacher is a role model for students so that what the teacher does will be imitated by the students. Therefore, a teacher must have good ethics. While students are people who seek knowledge. One of the sources that can be used by teachers and students in good ethics is the book Adabul 'Alim Wal Muta'allim by KH. Hasyim Asy'ari. This study will answer the questions: (1) What is the concept of Teacher and Student Ethics according to experts (2) What is the concept of Teacher and Student Ethics from the perspective of KH. Hasyim Asy'ari in the book Adabul 'Alim Wal Muta'allim This type of research is literature (books) or can be referred to as library research (library research) where this research is to collect data or scientific writings aimed at the object of research or data collection that is literature or a study carried out to solve a problem that is basically focused on critical and in-depth study of relevant library materials. The results showed that the Adabul 'Alim Wa Al Muta'alim book specializes in presenting the ethics of teachers and students in learning. The description focuses on the attitudes that a teacher must have when giving lessons both related to his students and to his book. The concept of teacher ethics in the book Adabul 'Alim Wa Al Muta'alim, among others: (1) Ethics for scholars (teachers) always draw closer to Allah, fear (khouf) of Allah's wrath, sakinah, wara', tawadhu' solemnly, always guided on God's law (2) Ethics when teaching, always going to the class assembly, greeting the entire audience, dealing with students with full attention, before starting teaching should read a few verses of the Qur'an, adjust the volume of the voice, (3) The teacher's ethics towards students, giving teaching, building sincere intentions, loving students, educating and teaching. While the ethics that must be possessed by a student include (1) Serang mirid must have a ta'dzim nature towards his teacher, (2) a student must be kind to his teacher (3). Reducing actions that are less useful (4) being serious in learning